Equity Research : Banco Espírito Santo Group - Mata, Ana Catarina Ferreira da (2013)
This investment advisory service is supported by some of the most adequate valuation frameworks discussed throughout the literature review, whose purpose is to break down the best quantitative assessment of the financial institutions’ equity and come up with a final price target. Thereby, an insightful analysis is provided, in which the source of research is a listed financial institution in PSI20 index – Banco Espírito Santo, the largest capitalised bank in Portugal. At the end of this dissertation, all the valuation metrics under analysis and the rational will be closely compared to Caixa Banco de Investimento’s banking report published on December 13 2011, an up-to-date sector report of the Portuguese banks challenges.